Capitalism, Communism, Environmentalism, and the Ideology of Freedom - Edward Sankowski; Betty Harris (Filozofia, 2023)
It has been common in some cultural contexts to distinguish sharply between capitalism and communism, assuming conflicting concepts of freedom. The dichotomy has influenced some philosophy, real-world contests in politics, and popular discourse. In the West, often capitalism and markets have been associated, however questionably, with freedom and democracy. Different notions of freedom have circulated as part of another ideological complex opposed to that of the West. However, environmentalisms of various sorts have increasing importance in suggesting newer types of freedom, previously less salient due to the overpowering capitalism-communism dichotomy. Abstract concepts of freedom influenced by the older capitalism-communism dichotomy need critique. Different environmentalisms, less centered on the old dichotomy, increasingly can be progressively connected with different freedoms-in-environments frameworks. New perceptions about freedom can emerge.